Gagasan Menyatukan Umat Islam Indonesia Melalui Kalender Islam - Susiknan Azhari (Universitas Islam Negeri Jakarta, 2015)
This article discussed many kinds of Islamic calendar in Indonesia, including Muhammadiyah, PBNU, Indonesia Taqwim Standard, and Islam PERSIS calendar. The results found each calendar has a different system in the initial launch of lunar month. Data reckoning found for 19 years (2015-2033) that it is differences possibilities for eight times. To resolve this discrepancy, the authors offered mutakamil Hilaltheory as a middle way between wujudul hilal and visibility, so the distinction has to be completed and the Eid can be universally implemented.DOI: 10.15408/ajis.v15i2.2869